A new species of the genus Anoplophora Hope (Coleoptera: Cerambycidae: Lamiinae: Lamiini) from Nanling Priority Area for Biodiversity Conservation - Lin, Mei-Ying; Wen, Dong (Zootaxa, 2024)
The diversity of the genus Anoplophora Hope, 1839 of Nanling Priority Area for Biodiversity Conservation is surveyed, with the discovery of one new species, A. xuei Lin & Wen, sp. nov. This species is described from Guangxi and Guizhou, China. Illustrations of the habitus and male genitalia of A. xuei Lin & Wen, sp. nov. and the similar A. leechi (Gahan) are provided. Additional locality data for A. leechi is provided.